Umfang des Winterdiensts bei Abwälzung auf die Anlieger. - (:unkn) unknown (Beck, 2001)
OLG Hamm, Urteil vom 16.8.2000 - 13 U 32/00. difu
Keywords: Winterdienst; Verkehr; Gemeindestraße; Fahrbahn; Gehweg; Anlieger; Räumpflicht; Streupflicht; Gemeindesatzung